Evaluation of anti‐factor Xa concentrations using a body mass index‐based enoxaparin dosing protocol for venous thromboembolism prophylaxis in trauma patients. Issue 3 (9th February 2022) - O'Keefe, Mary M.; Carver, Thomas W.; Herrmann, David J.; Prom, Alyson; Hubbard, Sara; Rein, Lisa E.; Peppard, William J.
Abstract: Objective: The aim of this study was to evaluate the effectiveness of a body mass index (BMI)‐based enoxaparin prophylaxis dosing protocol at achieving target anti‐factor Xa (anti‐Xa) concentrations in the trauma population. Methods: This retrospective chart review evaluated anti‐Xa concentrations in adult trauma patients who received prophylactic enoxaparin over a three‐month period. The primary outcome was the percentage of patients that achieved target anti‐Xa concentrations after ≥3 doses of enoxaparin. Secondary outcomes included correlations of anti‐Xa concentrations with enoxaparin dose per BMI, total body weight (TBW), and estimated blood volume (EBV). The prevalence of clinically relevant bleeding and venous thromboembolism was also recorded. Multivariable logistic regression was used to identify associated variables for target anti‐Xa concentration attainment. Results: Ninety‐nine consecutive patients were included in the study. Included patients were predominately male (69.7%) and Black (50.5%) with a mean age of 44.1 years. Target anti‐Xa concentrations were achieved in 62.6% of patients. Anti‐Xa concentrations were moderately correlated with enoxaparin dose per EBV ( ρ = 0.57), followed by dose per TBW ( ρ = 0.46), and dose per BMI ( ρ = 0.20). Multivariable logistic regression demonstrated that categorization of enoxaparin dose per EBV and per TBW were the only statistically significant predictors of reaching target anti‐Xa concentrations ( p = <0.001). Conclusions: In adult trauma patients, the rate of achieving target anti‐Xa concentrations remains suboptimal and provides room for further improvement. Enoxaparin dose per EBV was more closely correlated with anti‐Xa concentrations when compared to TBW and BMI. Dosing per EBV and TBW was the only variables associated with reaching target anti‐Xa concentrations within the study. Further investigation is warranted to elucidate optimal EBV‐ and TBW‐based dosing regimens.